Contributing causes to adverse events in home care and potential interventions to reduce their incidence. Issue 5 (September 2018) - Baker, G. Ross; Flintoft, Virginia; Wojtak, Anne; Blais, Regis
The increasing complexity of home care services, pressures to discharge patients quicker, and the growing vulnerabilities of home care clients all contribute to adverse events in home care. In this article, home care staff in six programs analyzed 27 fall- and medication-related events. Classification of contributing causes indicates that patient and environmental factors were common in fall events, while organization and management factors along with patient, task, team, and individual factors were common in medication-related events. Home care settings create specific challenges in identifying and mitigating risks. Some factors, such as variations in home environments, are difficult to address. However, changing care coordination structures and communication methods could ameliorate other factors, including poor communications among staff and limited team and cross-sector communication and coordination. Ensuring that medication ordering and administration processes are optimized for home environments would also contribute to safer care.